Unmasking Single-System Ectopic Ureter in Boys: Insights from a Decade at Kuala Lumpur General Hospital - Mohd Yusof, Muhammad Sakhawi; Nagappan, Poongkodi; Loi, Lynette (The Interventionalist Journal, 2026)
Single-system ectopic ureter is a rare congenital anomaly that primarily affects boys. Despite its low prevalence, it can lead to significant urinary tract complications if left untreated. This proposal aims to investigate the clinical presentation, diagnostic challenges, and optimal management strategies for single-system ectopic ureter among boys. By reviewing existing literature, analysing clinical cases, and exploring advancements in diagnostic imaging and surgical techniques, this research seeks to enhance our understanding of this condition and improve patient outcomes.